RELETIONSHIP BETWEEN FIVE ACTIONS INPLEMENTATION OF PIG FARMING WITH FARMERS PLASM INCOME LEVEL AT THE CHAROEN POKHPHAND LTD PARTNERSHIP PATTERN IN BALI - A. T. T., Sadhu; Inggriati, N. W. T.; Suparta, N. (Jurnal Peternakan Tropika; Vol 6 No 1 (2018): Vol. 6 No. 1 (2018), 2018)
Pig farming in Bali with partnership pattern is one of action that important for society prosperity, particulary in order to fulfill animal protein needs. Partnership pattern is one of government and private sectors action to support public livestock business. This experiment aim were, 1) to know level of five actions implementation, 2) to know income level, and 3) to know relationship between level of five actions implementation of pig farming with farmers plasm income level at the Charoen Pokhphand LTD partnership pattern in Bali. Respondents of the experiment were pig farmers that collaborate with the Charoen Pokhphand LTD in Bali that already spread at Tabanan, Badung, Gianyar and Bangli Regencies. Data respondents were collected to all population i.e 25 farmers. Data primer and seconder were insed in the experiment. To know relationship between five action with income level, the Spearman Scale Correlation Coefficient was used. Results of the experiment showed that implementation diet level offered had highly significant relationship (P<0,01) with income level of pig farmers of the Charoen Pokhphand LTD partnership pattern, while other factors such as total implementation level, implementation of germ, implementation level of disease, prevention, respondent ages, formal and informal educations had non significant relationship with income level of pig farming of the Charoen Pokhphand LTD. To increase implementation level of five actions of pig farming it needs to increase knowledge and good communicationintensity of instructor and among sesame farmers of the Charoen Pokhphand LTD partnership. Keywords : partnership, five actions, income level, pig farming